Acceptability of Medical Device Maintenance Management in Hospital Service Industry Based on the Diffusion of Innovation Theory - Ramli, Muhammad; Sentot, Bambang Jati; Yuliantini, Tine; Hasyim (ARE Publisher, 2024)
Objectives: The objectives of this study to determine the level of acceptance of health service managers of the WHO 2011 Programe maintenance system innovation.The level of adoption was studied by measuring the influence of innovation attributes and knowledge as moderators on the application of WHO 2011 Programe maintenance.Research is a Quantitative research with survey methods and causality techniques.Research from August - October 2019 with a research population of hospital service industries that have been accredited with KARS Plenary Accreditation with SNARS Standard 1 (2018). Methodology: The sample was taken with saturated sample technique. The sample is an individual who represents IPSRS Management, Electromedical Technicians and Medical Equipment Users.Innovation Attributes, Knowledge as a moderator and the level of Adoption are the Variables in the study.The research instrument uses a Likert scale.Validity test, Reliability test, Moderated Regression Analysis (MRA) test and Three box method are used in the study.All Variables are Reliable, Valid and there is no Multicollinierity between variables and all hypotheses are accepted. Finding: The WHO 2011 Programe maintenance aims to ensure better access, quality, and use of medical products and technology. The WHO 2011 Programe Maintenance Innovation Adoption Process by maximizing the functions of financial management, personnel management, operational management, performance monitoring and performance improvement is needed to form a good and measurable medical equipment maintenance system. Conclusion: There are differences in research results between previous research conducted by Everet Rogers, Bass and Mahajan et all with the results of the author's research. Knowledge Management is needed in accelerating the system adoption process in order to improve the effectiveness and achievement of medical equipment quality.